The Impact Of Community Radio As A Medium For Health Education And Disease Prevention In Rural Areas - Aminata Kamara; Abdul Karim; Amina Turay (Yayasan Adra Karima Hubbi, 2026)
Rural communities often face significant barriers in accessing timely and reliable health information, including limited healthcare infrastructure, low digital connectivity, and shortages of qualified health professionals. Community radio has emerged as an accessible medium capable of delivering health education and disease prevention messages tailored to local social and cultural contexts. This study aims to analyze the effectiveness of community radio as an educational intervention for improving public awareness, shaping preventive health behaviors, and fostering community engagement in rural health initiatives. A mixed-method approach was used involving surveys with 120 rural listeners, in-depth interviews with radio broadcasters and health workers, and content analysis of selected health programs aired over a three-month period. Results show that community radio significantly improved listener knowledge regarding infectious disease prevention, maternal and child health practices, and sanitation behaviors. Respondents reported increased confidence in applying preventive actions and greater participation in local health campaigns promoted through broadcasts. Qualitative findings further indicate that the use of local languages, storytelling formats, and trusted community figures enhances credibility and message acceptance. However, challenges such as inconsistent broadcast coverage, limited funding, and dependence on volunteer participation reduce program sustainability. The study concludes that community radio remains a powerful and culturally responsive tool for strengthening health literacy in underserved rural populations. Integrating radio-based health education with broader community health strategies and technological advancements, such as mobile interaction and social media extensions, can optimize effectiveness and long-term impacts. Conclusion. This study has significant implications for instructional practices in TFL settings and for L2 lecturers in the classroom. By understanding learners’ preferences for OCF, educators can tailor their instructional approaches to meet the specific needs of their students.